Total Recordable Injury and Incident Rate - Winda Trijayanthi Utama (Jurnal Kedokteran Universitas Lampung, 2020)
Indonesia is a country that has a high level of industrial development. This can be seen by the rapid growth and spread of industry, both on a small, medium, and large scale. The more rapid the industry is of course directly proportional to the emergence of challenges and problems in the industrial world. One of the challenges and problems that arise is how to deal with work accidents in a company environment. One of the efforts that can be made by companies to reduce the number of work accidents is to calculate work accidents. Calculation work accidents are fundamental in the world of occupational safety and health because the main objective of occupational safety and health is the prevention of occupational accidents and diseases. Total Recordable Injury and Incident Rate is a mathematical calculation of the total recordable incidents (above "first aid") multiplied by the multiplier constant (200,000 or 1,000,000) divided by the number of employee hours worked. Types of accidents or incidents that can be recorded or recorded according to the TRIR formula are the first aid (Medical Treatment Cases, Restricted Workday and Transfer Activity Cases, Lost Workday Cases and Fatalities).Keywords: Total Recordable Injury, Incident Rate, Medical Treatment Cases, Restricted Workday and Transfer Activity Cases, Lost Workday Cases and Fatalities.